2021
DOI: 10.1021/acssensors.1c01088
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid and Sensitive CasRx-Based Diagnostic Assay for SARS-CoV-2

Abstract: The development of an extensive toolkit for potential point-of-care diagnostics that is expeditiously adaptable to new emerging pathogens is of critical public health importance. Recently, a number of novel CRISPR-based diagnostics have been developed to detect SARS-CoV-2. Herein, we outline the development of an alternative CRISPR nucleic acid diagnostic utilizing a Cas13d ribonuclease derived from Ruminococcus flavefaciens XPD3002 (CasRx) to detect SARS-CoV-2, an approach we term SENSR (sensitive enzymatic n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…This can be attributed mainly to the nonspecific collateral cleavage activity of CRISPR-Cas systems that complicates the integration of more than one reporter in a single reaction. Therefore, in many cases, several separate and independent reactions are developed to detect different targets or internal controls ( 29 , 42 , 43 ). The development of a one-pot multiplexed detection reaction is of great importance to improve the detection efficiency, accuracy, and clinical applicability of CRISPR-based diagnostics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed mainly to the nonspecific collateral cleavage activity of CRISPR-Cas systems that complicates the integration of more than one reporter in a single reaction. Therefore, in many cases, several separate and independent reactions are developed to detect different targets or internal controls ( 29 , 42 , 43 ). The development of a one-pot multiplexed detection reaction is of great importance to improve the detection efficiency, accuracy, and clinical applicability of CRISPR-based diagnostics.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the wide use of CRISPR-Cas13 enzymes for in vivo applications ( 55 ), Cas13 proteins have been increasingly used to develop various diagnostic platforms ( 41 ), and their usefulness for the development of diagnostics has become apparent during the COVID-19 pandemic ( 30 32 , 56 58 ). LAMP isothermal amplification was adapted to develop sensitive CRISPR diagnostics for SARS-CoV-2 detection, including DETECTR ( 29 ), iSCAN ( 59 ), DISCoVER (Cas13-based module) ( 30 ), and an FDA-authorized CRISPR-Cas13–based diagnostics test (SHERLOCK CRISPR SARS-CoV-2 Kit; Integrated DNA Technologies).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers reported that a CRISPR‐based system using an enzyme called Cas13d can diagnose SARS‐CoV‐2 in less than an hour. The technology could be included in lateral flow tests, may be more appropriate for resource‐poor settings than current diagnostic methods and could help identify emerging pathogens 11 …”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…The technology could be included in lateral flow tests, may be more appropriate for resource-poor settings than current diagnostic methods and could help identify emerging pathogens. 11 "The therapeutic applications of CRISPR are starting to reach clinical trials and can be broadly divided into two camps," Qasim says. "One, where cells are collected from patients or donors, engineered using CRISPR, and then infused into patients.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Moreover, with the help of a single liquid-handling robot, the high-throughput assay can process up to 5000 samples per day. Despite Cas13a being used in RNA virus detection, Cas13d was also developed into a SARS-CoV-2 diagnostic assay, termed the Sensitive Enzymatic Nucleic-acid Sequence Reporter (SENSR) [39]. SENSR required an initial isothermal preamplification reaction combining RT-RPA producing a short dsDNA amplicon encompassing the Cas13d target site and containing a T7 promoter sequence.…”
Section: Conventional Rna Virus Diagnosticsmentioning
confidence: 99%